A systematic mapping review of factors associated with willingness to work under emergency condition - Hamideh Nafar; Emir Tahmazi Aghdam; Naser Derakhshani; Nadia Sani'ee; Sakineh Sharifian; Salime Goharinezhad (BMC, 2021)
Abstract Introduction An effective response to an emergency situation relies on health care workers' preparedness. The main purpose of this study was to provide a comprehensive overview of relevant studies regarding the willingness to work in emergency and disaster situations, describe and classify the most important challenges and solutions, identifying knowledge gaps in the literature which could inform future research. Methods In this Systematic Mapping Review required information was searched from PubMed, Scopus, the web of science, Embase databases, and Google scholar search engine in the period 2000-2020. Data were analyzed using a content framework analysis. Results From 2902 article search results, 26 articles met the inclusion criteria. The studies varied in terms of aim, study design, and detail of reporting. The results showed that nearly three-quarters of studies were conducted in high and middle-income countries. Most of the studies were published in 2020 due to the COVID-19 pandemic. Also, the most common types of crises reported in the included studies were emerging and re-emerging infectious diseases. The results show that most of the problems were in the dimension of mental and psychological issues, personnel health concerns, and management relationship with personnel. Conclusion This mapping review illustrated a big picture of health workers' resilience in disaster conditions. This review presents an overview of different kinds of strategies that address the challenges. One of the most important challenges in health workforce retention is poor communication between managers and staff. Being away from family, which leads to mental fatigue, puts staff in moral dilemmas. Attracting adequate health professionals, especially volunteers and regulating the shifts of health personnel in crisis time will largely prevent burnout.